Dual-Mode Reconfigurable Frequency-Selective Surface for Switching Between Narrowband and Wideband Applications - Uslu, Batuhan; Keskin, Sena Esen Bayer; Tokan, Nurhan Turker (MDPI, 2025)
This study presents a reconfigurable frequency-selective surface (R-FSS) designed to dynamically switch between WLAN, WiMAX, and sub-6 GHz band frequencies. The electronic switching mechanism of this R-FSS is controlled in real-time using PIN-diodes. Depending on the activation state of these diodes, the structure operates in three distinct modes. Among the three modes, one exhibits polarization-stable wideband suppression, whereas the other two demonstrate polarization selectivity by interchanging between the dual-narrow and single-wide stopband regimes under orthogonal polarizations. The design is described with an equivalent-circuit model, corroborated by full-wave electromagnetic simulations, and validated through measurements of a fabricated prototype. This reconfigurability allows the proposed structure to operate across WLAN, sub-6 GHz, and WiMAX frequency ranges either with two narrow stopbands or with a single-wide stopband, while providing polarization selectivity for frequency-selective applications.
Keywords: dual-mode; wideband; reconfigurable; FSS; PIN-diode; dynamic switching; Chemistry; Science & Technology - Other Topics; Instruments & Instrumentation; Physics